Metal and graphene hybrid metasurface designed ultra-wideband terahertz absorbers with polarization and incident angle insensitivity. Issue 4 (5th February 2019) - Peng, Lin; Li, Xiao-ming; Liu, Xiao; Jiang, Xing; Li, Si-min
Abstract : In this research, a new technique for ultra-wideband (UWB) absorber design is proposed. Our design approach includes a metal metasurface and a graphene metasurface. It is found that the hybrid metal and graphene metasurfaces trap very wideband EM waves in the structure, which contributes to UWB wave absorption. Abstract : Terahertz electromagnetic (EM) wave absorbers are vital in photonics, however, they suffer from limited bandwidth. A new approach for ultra-wideband (UWB) terahertz absorber design is proposed with metal and graphene metasurfaces. The UWB characteristics are owing to three factors: (1) the metal metasurface boosts the surface plasmon-polaritons (SPPs) of the graphene metasurface which leads to confined field enhancement, (2) the merging and interaction of the resonances of the metal and graphene metasurfaces, and (3) the multiple reflections and superpositions between the metasurfaces and the gold layer. A prototype designed using a dual-ring metal metasurface, fishnet graphene metasurface, polyimide substrate and gold reflecting layer is proposed. One cell of the prototype includes one metal dual-ring unit and four graphene fishnet units. The proposed absorber has an UWB bandwidth of 6.46 THz (145%) for absorptivity larger than 0.9, with a high octave of 6.21. The proposed absorber is also insensitive to the polarization state and incident angle of the illuminating EM waves. Besides, the amplitude modulation depth in the 5–6 THz band is up to 95.4%. The physical mechanisms of the wideband operation are also discussed. The research in this work could offer a new thought for UWB absorber design, and has potential applications in terahertz imaging, sensors, photodetectors and modulators ( e.g. [L. Peng, X. M. Li, X. Liu, X. Jiang and S. M. Li, Nanoscale Adv., 2000, 35, 3523]).